DEVELOPING STUDENT CREATIVE ACTIVITY BASED ON PROBLEM EXPERIENCES IN THE DIGITAL EDUCATIONAL SPACE - Burkhiev Olimjon Boboyevich (Journals Park Publishing, 2025)
This DSc-level scientific article provides a comprehensive analysis of the theoretical, methodological, cognitive, and technological foundations for developing student creative activity through problem-based experiences in the digital educational environment. The study investigates the mechanisms through which digital platforms—such as simulation environments, project-based digital studios, gamified problem scenarios, interactive AI-based systems, and virtual collaborative workspaces—stimulate creativity, divergent thinking, cognitive flexibility, metacognitive awareness, and innovative problem-solving skills. Structured according to the IMRaD model and aligned with OAK academic requirements, the research synthesizes constructivist, socio-digital, neurocognitive, and experiential learning theories to explain how digital problem-based experiences transform traditional learning into a creativity-centered process. Findings reveal that digital problem-based tasks significantly increase idea generation, originality, creative risk-taking, multimodal expression, and algorithmic reasoning, while strengthening learners’ autonomy, digital literacy, and adaptive competence. The study concludes that digital educational ecosystems provide a rich and dynamic environment that supports the continuous development of creativity as a core 21st-century competency.
Keywords: Digital education, creativity, problem-based learning, cognitive flexibility, innovation, experiential learning.